Socio-Cultural Factors Influencing Uptake of Skilled Childbirth Services among Women in Kaiti Division, Makueni District (Kenya) - Anthony Wambua Mathulu; Benard Wambua Mbithi (Intelektual Pustaka Media Utama, 2017)
Each year, over 500,000 women die from the complications of pregnancy and child birth, almost all of them in the developing countries. This trend can be addressed by increasing the rates of skilled care during childbirth. This study therefore sought to establish the socio-cultural factors influencing uptake of skilled childbirth care which has remained low in Kaiti Division. The researchers applied a descriptive cross-sectional study design which involved women of childbearing age (15-49 years). The study was conducted in March 2010 and had a sample size of 246 women which was randomly selected from the estimated target population of 12,077. The researchers applied both quantitative and qualitative approaches. The tests of significance employed included Fisher’s exact test, chi-square, test and logistic regression. The study established that the proportion of women attended to by the skilled attendant within various age cohorts was higher (58.9%) amongst the youth/adolescent (15-24 years) (P-value = 0.091> 0.05, c2 10.915 df 6).). Skilled attendance declined among the grand-multiparas (para4 and above) from 7.7% in Para 4-5 to 2% in Para 6+ (P-value = .000<0.05, c2 34.888 df 3; Para 1(p =0.000, OR 28.391), Para 2-3 (p =0.000, OR 7.564), Para 4-5(p=0.030, OR 3.493) Further findings indicated that the principal decision maker (46.7%) on type of assistant in the last delivery was the woman (P-value = 0.000 <0.05, c2 56.076 df 5). However, the husband was the leading (39.5%) decision maker in use of a skilled assistant in the last delivery (p=0.000, OR 15.667). More than two thirds (70.7%) of the respondents who performed a ceremony prayed for safe delivery in their last delivery. The study concluded that women’s parity, decision making and religion were significant in use of skilled childbirth services.